Solvent and substituent effects on the thermolysis of antimalarial fluorophenyl substituted 1,2.4-trioxanes - Cafferata, Lázaro F. R. (2003)
The kinetics and mechanism of the thermal decomposition reaction of cis-6-(4-fluoropheny1)-5,6-[2-(4-fluorophenyl)-propylidene]-3, 3-tetramethylene-1,2,4-trioxacyclo-hexane (I) were investigated separately in n-hexane and in methanol solutions over the temperature and concentration ranges of 393.2-443.2 K and 2.7-54 × 10-5 M, respectively. The values of the activation parameters for both reactions were compared with the corresponding ones for the thermolysis of cis-6-(4-fluorophenyl-5,6-[2-(4- fluorophenyl)-3-hydroxypropylidene]-3,3-tetramethylene-1,2,4-trioxacyclohexane (II), investigated in the same solvents and temperature range. Substituent and solvent effects on the initial homolytic rupture of the O-O peroxydic bonds of those molecules were evaluated.